2015
DOI: 10.1111/omi.12138
|View full text |Cite
|
Sign up to set email alerts
|

QseBC, a two‐component bacterial adrenergic receptor and global regulator of virulence in Enterobacteriaceae and Pasteurellaceae

Abstract: SummaryThe QseBC two‐component system (TCS) is associated with quorum sensing and functions as a global regulator of virulence. Based on sequence similarity within the sensor domain and conservation of an acidic motif essential for signal recognition, QseBC is primarily distributed in the Enterobacteriaceae and Pasteurellaceae. In Escherichia coli, QseC responds to autoinducer‐3 and/or epinephrine/norepinephrine. Binding of epinephrine/norepinephrine is inhibited by adrenergic antagonists; hence QseC functions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 71 publications
1
44
0
Order By: Relevance
“…in iron-overloaded media in response to catecolamines (Weigel et al, 2015) as well as an activator of motility (Weigel and Demuth, 2016), a phenotype that is induced in iron-overloaded human serum (Table 3 and Supporting Information Fig. S2B).…”
Section: Discussionmentioning
confidence: 99%
“…in iron-overloaded media in response to catecolamines (Weigel et al, 2015) as well as an activator of motility (Weigel and Demuth, 2016), a phenotype that is induced in iron-overloaded human serum (Table 3 and Supporting Information Fig. S2B).…”
Section: Discussionmentioning
confidence: 99%
“…Defects in the type III secretion system render a bacterium non-pathogenic (Gong et al, 2010); the QseBC two-component system was associated with bacterial quorum sensing and virulence factors expression (Weigel and Demuth, 2015). We observed that decreased gene relative abundances for the type III secretion system and the QseBC two-component system were mainly assigned to Escherichia , which exerts a barrier effect against enteropathogens (Hudault et al, 2001), and are responsible for providing vitamin K2 (Meganathan, 2001), suggesting a depleted beneficial metabolism from Escherichia in diarrheic piglets.…”
Section: Discussionmentioning
confidence: 99%
“…This activation leads to increased expression of genes responsible for biofilm growth, the expression of flagella and motility as well as other virulence genes [21]. Furthermore, QseBC expressed by H. influenzae responds to ferrous iron, but not catecholamines [23].…”
Section: Two-component System (Qsebc)mentioning
confidence: 99%
“…There is also evidence that the two-component system QseBC is activated in the presence of iron-catecholamine complexes, leading to an induction of genes responsible for anaerobic metabolism and respiration and a down regulation in genes encoding iron acquisition [21]. This is possibly a result of the bacteria sensing an iron rich environment and spends less energy in trying to bring in large amounts of iron.…”
Section: E Significancementioning
confidence: 99%